A General Approach to Probe Dynamic Operation and Carrier Mobility in Field‐Effect Transistors with Nonuniform Accumulation. (22nd May 2019) - Liu, Chuan; Chen, Changdong; Li, Xiaojie; Hu, Sujuan; Liu, Chenning; Huang, Kairong; Dai, Fuhua; Zhang, Baijun; Liu, Xuying; Minari, Takeo; Noh, Yong‐Young; Chen, Jun
Abstract: Revealing the intrinsic electrical properties is the basis of understanding new functional materials and developing their applications. However, in nonideal field‐effect transistors (FETs), conventional current–voltage characterizations do not accurately probe charge transport, particularly for newly developed semiconductors. Here, a generalized gated four‐probe (G‐GFP) technique is developed, which detects dynamic changes in carrier accumulation and transport. The technique is suitable for exploring the intrinsic properties of semiconductors in FETs with arbitrary contacts and in any operational regimes above the threshold. Application to simulated transistors confirms its accuracy in probing the evolution of channel potential, drift field, and gate‐dependent carrier mobility for devices with a contact‐limited operation and disordered semiconductors. Comparative experiments are performed based on FETs with various materials, device structures, and operational temperatures. The G‐GFP technique proves to exclude the various injection properties, to detect in situ how carriers are accumulated, and to clarify carrier mobility of the semiconductors. In particular, the well‐known "double‐slope" features in the current–voltage relations are controllably generated and their origins are identified. The approach could be used to explore electronic properties of newly developed materials such as organic, oxide, or 2D semiconductors. Abstract : To reveal the intrinsic mobility of advanced semiconductors and the origin of nonideality of field‐effect transistors (FETs), a generalized gated four‐probe (G‐GFP) technique is developed. It detects dynamic accumulation and carrier transport in FETs with arbitrary contacts and in any operational regimes above the threshold.